Re-description and first host and biology records of Entedon magnificus (Girault & Dodd) (Hymenoptera, Eulophidae), a natural enemy of Gonipterus weevils (Coleoptera, Curculionidae), a pest of Eucalyptus trees - Gumovsky, Alex; Little, Dave De; Rothmann, Sergio; Jaques, Lorena; Mayorga, Sandra Elizabeth Ide (Zootaxa, 2015)
Entedon magnificus (Girault & Dodd) (Hymenoptera: Eulophidae, Entedoninae) is recorded as a gregarious larval endoparasitoid of Gonipterus weevils (Coleoptera: Curculionidae), significant pests of Eucalyptus trees. Entedon magnificus is re-described and illustrated based on females and males from Australia and Tasmania.